STRATEGI PEMBELAJARAN QUR’AN HADITS DALAM PENCAPAIAN KOMPETENSI SISWA DI MAN 3 NGANJUK - Rasela, Fitrianti; Muslih, Imam (Al Tadib : Jurnal Ilmu Pendidikan, 2018)
Abstract: This article discusses the Qur'an Hadith learning strategy in achieving student competenceXI Religion in MAN 3 Nganjuk and associated with it. With case study model and descriptivequalitative research approach, research tried to dig data by using interview technique, observation,and documentation. Data analysis using data reduction procedures, data presentation, dataverification. Technique of checking of data validity by doing extension of observation, increasingpersistence and triangulation. The result of the research shows that learning strategy of Qur'an Haditsin the achievement of student competence in MAN 3 Nganjuk following learning evaluation, readingBTA, memorizing and understanding Al-Qur'an and Hadith, and achievement of student competencein MAN 3 Nganjuk succesfully enough and constructively . This is evident by looking at the finalscore of the exam results and the explanation from the teacher of the Qur'an Hadith, although thereare still some students who still can not understand optimally, but from the madrasah still strives sothat it can meet the target to be conveyed by the school. Supporting factors are the availability ofbooks of amma, companion teachers, libraries and printed copies of the Qur'an, and the inhibitingfactors are the lack of awareness of the importance of Qur'an Hadith, Lack of motivation, limitedmaterial, and limited time availability.Keywords: Learning Strategy, Competency Achievement Abstrak: Artikel ini membahas strategi pembelajaran Qur’an Hadits dalam pencapaian kompetensisiswa XI Agama di MAN 3 Nganjuk dan yang terkait dengannya. Dengan model studi kasus danpendekatan penulisan kualitatif deskriptif, penulisan mencoba menggali data dengan menggunakanteknik wawancara, observasi, dan dokumentasi. Analisis data menggunakan prosedur reduksi data,penyajian data, verifikasi data. Teknik pengecekan kebsahan data dengan melakukan perpanjanganpengamatan, meningkatkan ketekunan dan triangulasi. Hasil penulisan menunjukan bahwa strategipembelajaran Qur’an Hadits dalam pencapaian kompetensi siswa di MAN 3 Nganjuk berikutevaluasi pembelajaran, membaca BTA, menghafal dan memahami Al-Qur’an dan Hadits,dan pencapaian kompetensi siswa di MAN 3 Nganjuk berhasil dengan cukup baik dan konstruktif. Initerbukti dengan melihat nilai akhir hasil ujian dan penjelasan dari Guru mata pelajaran Al-Qur’anHadits, meskipun masih ada sebagian siswa yang masih belum bisa memahami secara optimal,namun dari pihak madrasah tetap mengupayakan sehingga bisa memenuhi target yang ingindisampaikan oleh sekolah. Faktor pendukung adalah tersedianyanya buku juz amma, gurupendamping, perpustakaan dan buku cetakan AL-Qur’an, dan faktor penghambat adalah kurangnyakesadaran tentang pentingnya Al-Qur’an Hadits, Kurangnya motivasi, materi terbatas, danketersediaaan waktu yang terbatas. Kata Kunci : Strategi Pembelajaran, Pencapaian Kompetensi